1996
DOI: 10.1021/ma9517207
|View full text |Cite
|
Sign up to set email alerts
|

Poly(hydroxy amide ethers):  New High-Barrier Thermoplastics

Abstract: The synthesis of a new class of high-barrier polymers, poly(hydroxy amide ethers), is described. The polymers are formed by the reactions of bisphenol-A diglycidyl ether, OCH2CHCH2OC6H4C(CH3)2C6H4OCH2CHCH2O, and amide-containing bisphenols of the general formula HOC6H4NHC(O)RC(O)NHC6H4OH [R = −(CH2) n −, −CH2C6H4CH2−, or −C6H4−] or HOC6H4NHC(O)C6H4OH at 140−160 °C in propylene glycol monophenyl ether solvent using ethyltriphenylphosphonium acetate as initiator. High-molecular-weight poly(hydroxy amide ethers) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 25 publications
2
54
0
Order By: Relevance
“…[8] Further, although we and others have shown that reactions of ADGE with bisphenols afford a stunning variety of poly(hydroxyethers) (see Sec. 4) comparable in molecular weight to those prepared by the direct sequence of Scheme 1, [9,10] we have found that polymerizations of ADGE with dinucleophilic amines, [11] dicarboxylic acids, [12] dithiols, [6] and disulfonamides [13] often yield polymers with combinations of barrier performance and other properties that cannot be realized with poly(hydroxyethers), at least without resorting to unusual and commercially unavailable bisphenols. [6] Of special interest are poly(hydroxyaminoethers), recently commercialized under the tradename BLOX Adhesive and High-Adhesion Barrier Resins (trademark of the Dow Chemical Company).…”
Section: Introductionmentioning
confidence: 90%
“…[8] Further, although we and others have shown that reactions of ADGE with bisphenols afford a stunning variety of poly(hydroxyethers) (see Sec. 4) comparable in molecular weight to those prepared by the direct sequence of Scheme 1, [9,10] we have found that polymerizations of ADGE with dinucleophilic amines, [11] dicarboxylic acids, [12] dithiols, [6] and disulfonamides [13] often yield polymers with combinations of barrier performance and other properties that cannot be realized with poly(hydroxyethers), at least without resorting to unusual and commercially unavailable bisphenols. [6] Of special interest are poly(hydroxyaminoethers), recently commercialized under the tradename BLOX Adhesive and High-Adhesion Barrier Resins (trademark of the Dow Chemical Company).…”
Section: Introductionmentioning
confidence: 90%
“…However, EVOH properties, including barrier properties, are greatly affected by water content. 1,2 Because water is always present in a food packaging system (it forms part of the external atmosphere and is a main constituent of many foodstuffs), EVOH films are always sandwiched between polyolefin layers (barrier to water) to protect EVOH. In some cases, both package and food are subject to thermal treatments such as pasteurization or retorting.…”
Section: Introductionmentioning
confidence: 99%
“…32,41,[46][47][48][49][50][51][52][53][54][55][56][57][58] However, various synthetic methodologies were used during their preparation and complete characterization was not carried out in most cases. In this work, diglycidyl ethers 6-22 were prepared using the same synthetic procedure and were fully characterized by a combination of NMR methods and epoxide equivalent weight determination.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(hydroxy amide ethers) 23-39 (Table Scheme 1 4) were prepared by the reactions of N,N′-bis(3-hydroxyphenyl)adipamide (5) with diglycidyl ethers 6-22 using a previously described synthetic methodology 26 ) with the use of an ethyltriphenylphosphonium acetate-acetic acid complex (70% in methanol) as catalyst. During the polymerization reaction, the phe- nolic groups react with the epoxide functionalities, generating the pendent secondary hydroxyl groups along the polymer backbone.…”
Section: Resultsmentioning
confidence: 99%